ANALISIS PENGARUH E-SERVICE QUALITY, E-RECOVERY SERVICE QUALITY TERHADAP LOYALITAS MELALUI PERCEIVED VALUE SEBAGAI VARIABEL MEDIASI (STUDI PADA PELANGGAN SHOPEE DI KOTA PADANG) - Amelia Eka Putri; Verinita Verinita (Departemen Manajemen, 2019)
This study aimed to determine the effect of e-service quality, e-recovery service quality on loyalty through perceived value as mediating variable in Shopee customers in Padang. This research is explanatory with quantitative methods. The sampling technique used in this study was purposive sampling for customers who had shopped at Shopee sites at least three times, with a sample of 150 respondents. This study uses Partial Least Square with the SmartPLS 3.0 program. The results showed that e-service quality, e-recovery service quality had an effect on perceived value. Perceived value influences loyalty. E-service quality does not affect the loyalty, while e-recovery service quality effect on loyalty. E-service quality does not affect loyalty through perceived value as a mediating variable. Furthermore perceived value mediated relationship between e-recovery service quality and loyalty through. The implication of this research is to increase consumer loyalty to the marketplace site by increasing the quality of electronic services, the quality of electronic service recovery, and the perception of customer value. In general, the quality of services provided by Shopee is good, but there are several indicators that need to be considered and improved.